PREFIXES FOUND ON SELECTED BARACK OBAMA’S INSTAGRAM CAPTION: MORPHOLOGICAL STUDY - Ida Bagus Made Sadu Gunawan; Winarta, Ida Bagus Gde Nova; Prawita, Ni Ketut Riska Dewi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
ABSTRACT The purpose of this study was to interpret and describe the prefix type from Barack Obama's Instagram caption. It is because Barack Obama have good personal in the public, such as he is win the Nobel Peace Prize and third to win a Nobel Prize while in office. The name Barack means